Genetic variability in the microRNA binding sites of BMPR1B, TGFBR1, IQGAP1, KRAS, SETD8 and RYR3 and risk of breast cancer in Colombian women - Garcia Mesa, Karen; Lorenzo Bermejo, Justo; Torres, Diana; Gilbert, Michael; Plass, Christoph; Hamann, Ute (OncoTargets and therapy, 2020)
Genetic Variability in the microRNA Binding Sites of BMPR1B, TGFBR1, IQGAP1, KRAS, SETD8 and RYR3 and Risk of Breast Cancer in Colombian Women